2012
DOI: 10.1186/2008-2231-20-62
|View full text |Cite
|
Sign up to set email alerts
|

Financial perspective of private pharmacies in Tehran (Iran); is it a lucrative business?

Abstract: Background and purpose of the studyPharmacies as direct providers of medicine and pharmaceutical services to patients have an important role in the health status of a society. The assessment of their financial situations by healthcare policy makers is necessary to prevent any negative effects on population's health. In this study we aim to analyze the financial status of pharmacies in Tehran, Iran.MethodsThis study is a cross-sectional study based on a survey. Two-hundred and eighty-eight private community day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Pharmaceutical companies and distributers depend upon costumers for the power required to carry out their will. They usually use marketing strategies or offer discounts to in uence the pharmacy (29). Sometimes pharmaceutical companies use the power of patient associations and customers to persuade a prescriber or pharmacy to prescribe or sell a particular brand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical companies and distributers depend upon costumers for the power required to carry out their will. They usually use marketing strategies or offer discounts to in uence the pharmacy (29). Sometimes pharmaceutical companies use the power of patient associations and customers to persuade a prescriber or pharmacy to prescribe or sell a particular brand.…”
Section: Discussionmentioning
confidence: 99%
“…There are two kinds of main competitors arising out of the business pro le of PCPs including public and private pharmacies. More than 80% of active pharmacies in Iran are nanced privately and the excess are owned by public organizations or institutions such as medical universities or Iran Red Crescent (29).…”
Section: Discussionmentioning
confidence: 99%
“…Some other infrastructural requirements including nondiscriminating laws supporting competition, the competitive pricing policy, the presence of international companies in the market, and full privatization of companies had to be also considered by policy makers to approach their goal. As an example, the current pharmaceutical pricing model in Iran has lead the companies to compete each other on giving more financial incentives to pharmacies to sell their products[ 17 ] which reduces their profitability and negatively affects their efficiency. A study has shown that pharmaceutical companies have also not been successful in using the potentials of branding.…”
Section: Discussionmentioning
confidence: 99%
“…As for criteria to assess community pharmacy performance, local researches have studied pharmacist's satisfaction, clients' satisfaction and financial results, including costs, income and profitability. [49][50][51] Noticing this situation, the main aim of this study was to provide decision makers and pharmacy managers with a broader perspective on related issues. Table 1 Variables identified through literature review (intra-and extra-organisational factors affecting the outcomes of an organisation and criteria to assess organisational performance)…”
Section: Community Pharmacy Profession In Iranmentioning
confidence: 99%